Penggunaan Data Citra Landsat Multitemporal untuk Monitoring Kondisi Ekosistem Mangrove di Teluk Kulisusu Kabupaten Buton Utara - Mohammad Ashari Dwiputra; Rahmat Kurnia; Etty Riani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
Scientific information mangrove ecosystem at Kulisusu bay was limited. This study aims to identify mangrove ecosystems area change at Kulisusu bay within 20 years periods (1995-2015) using satellite imagery Landsat 5 TM (1995), Landsat 7 ETM (2005) and Landsat 8 OLI (2015). Analysis of the mangrove ecosystem changes was used NDVI algorithm then carried classification canopy density by three classes, high, medium and low density.The changes of mangrove ecosystems were based on the area changes of each 10 year. The NDVI results shown that on 1995 to 2005, high and medium classes were reduced respectively by 340 ha and 36 ha, low class area was 172 ha. The period within 2005 to 2015 shows that high areas were reduced by 756 hectares, then medium and low density class 22 Ha and 680 ha respectively. Conditions mangrove ecosystem during 30 years was from 1995 to 2015 shown that had been a heavy reduction in the high density class about 1096 hectares, a reduction of medium density class was 14 hectares and low class was 852 Ha. The amount of reduction in high density class was caused by the mangrove logging activities for charcoal used as raw materials, and fisherman activities likes boat lines for crab fishing ground in the mangrove ecosystem. Keywords: mangrove, NDVI, GIS, Kulisusu Bay